2010
DOI: 10.1016/j.jvs.2010.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The Minimally Invasive Management of Visceral Artery Aneurysms and Pseudoaneurysms

Abstract: years) and 125 women (mean age, 70.0 Ϯ 11.2 years; P ϭ NS). Women were more likely to undergo treatment for critical limb ischemia (87.7% vs 77.7%; P ϭ .028) and less likely to have treatment for claudication (12.3% vs 22.3%; P ϭ NS). Women were also more likely to undergo balloon angioplasty (57.5% vs 68.9%; P ϭ .043). However, men were more likely to have coronary disease, history of coronary bypass grafting, and chronic renal insufficiency. TransAtlantic Intersociety Consensus distribution, incidence of smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 0 publications
1
63
0
1
Order By: Relevance
“…While the natural history of these aneurysms is not well known as many are found incidentally on studies performed for other reasons, a definite risk of rupture has been demonstrated. [5][6][7][8][9] Depending on size and location, mortality from rupture ranges from 25-100%. 1,6 Treatment recommendations are based on the specific artery affected.…”
Section: Introductionmentioning
confidence: 99%
“…While the natural history of these aneurysms is not well known as many are found incidentally on studies performed for other reasons, a definite risk of rupture has been demonstrated. [5][6][7][8][9] Depending on size and location, mortality from rupture ranges from 25-100%. 1,6 Treatment recommendations are based on the specific artery affected.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical intervention is one option for the treatment of pseudoaneurysms of the visceral arteries; however, the risk of post-operative complications in this patient population can increase the chance of a poor surgical outcome. 8 This is the first reported case describing the endovascular management of a common hepatic to proper hepatic artery saphenous vein interposition graft anastomotic blowout. Transcatheter embolization or stent placement offers a viable treatment alternative to traditional surgery.…”
Section: Discussionmentioning
confidence: 91%
“…A century later, in 1871, German surgeon Heinrich Quincke described the clinical signs of haemobilia caused by the rupture of a hepatic artery aneurysm . Today, visceral artery aneurysms (VAAs) are still considered rare, with an incidence of between 0.01% and 2% of all autopsies and angiographic series . The term encompasses both true and false aneurysms of the coeliac axis, superior mesenteric artery, inferior mesenteric artery and their branches.…”
mentioning
confidence: 99%
“…As the pseudoaneurysm was noted to be fairly superficial, it was initially injected with thrombin percutaneously, and an abdominal Doppler USS performed immediately after revealed adequate pseudoaneurysm occlusion . However, a follow‐up abdominal Doppler USS performed 2 days later revealed a small area of patency through the initially occluded pseudoaneurysm, with blood flow into the patent area.…”
mentioning
confidence: 99%
See 1 more Smart Citation